“It’s All French Over There”: My Quest for Franco-Ontarians around Lake Erie - Anderson, Roger (Journal of International Students, 2023)
This narrative recounts one U.S. professor of French quest to locate French-speaking communities of Ontario, Canada. After one week of wasted travel and repeated frustration from misguided tips, one brief but spectacular moment occurred in a village grocery store. It upended his pre-conceived understanding of this group and their linguistic practices. Drawing from sociological theories Bourdieu, Foucault, and Bronfenbrenner’s Ecological Systems Theory, the author analyzes the totality of his quest, from exasperation to enlightenment. This cross-border narrative demonstrates that even highly educated individuals can be ineffective within new ecological systems because of their inability to recognize the influence of their own microsystems. Analysis suggests that a network configuration of Bronfenbrenner’s model, rather than a nested one, more accurately reflects this linguistic landscape. Finally, Foucault’s heterotopia helps explain the misrecognition of community’s language practices. The essay subsequently offers advice to quest-takers, those seeking to understand /belong to a new culture.